EFL Writing Strategies of the Second Year Students of SMPIT Daarul ‘Ilmi Kemiling Bandar Lampung - Muhammad Rudy (International Conference on Education and Language (ICEL), 2013)
This research is aimed to observe the writing strategies which occur in the writing process. The subjects were managed to do think aloud. The recorded verbalization is used to gain the data. After the analysis process, the result shows that writing difficulties influence the strategies used and lead the subjects to engage several strategies for creating a sentence.